The Comprehension of Tempo’s Newspaper English Article for the 10th Grade Students at Al-Qomariyah Boarding School - Frainskoy Rio Naibaho; Lely Fitri Hasibuan; Mahardika Abdi Prawira Tanjung (LPPM IAKN Tarutung, 2022)
This study deals with the comprehension of Tempo’s Newspaper English Article for the 10th Grade Students at Al-Qomaiyah Boarding School. It was aimed to know the ability of students in comprehend of Tempo’s Newspaper English article. The data of this study were the score of students and the source od this study was the twenty students of Al-Qomariyah Boarding School. Observation, Interview, and test were used to obtain the data. the data were analyzed by using Miles and Huberman (1992). Based on the data analysis,the ability of the students in comprehension the English language article still tend to be weak, it can be seen from more than students who choose to translate the article rather than understand it.